Experimental demonstration on long-range time-reversal multiple-input/multiple-output underwater acoustic communication over tens of kbps in 12.5 km range. (1st July 2022) - Kida, Yukihiro; Deguchi, Mitsuyasu; Shimura, Takuya
Abstract: In this paper, the adaptive time reversal (ATR) technique combined with a single channel decision feedback equalizer (DFE) is applied to an at-sea experiment of the underwater acoustic multiple-input/multiple-output (MIMO) communication utilizing the signal bandwidth of 4.5–8.5 kHz over the distance of 12.5 km. This paper focuses on the demonstration of the effectiveness of the spatial division multiplexing MIMO using ATR-DFE schemes in time-varying real sea environment, and how much the communication rate could be achieved, with changing the signal parameters. We report that the communication quality is dependent on the duration from the channel probing for ATR process to signal reception, and we found that the output signal-to-noise ratio of the demodulated results highly correlated to the temporal coherence of the acoustic channel. Finally, the relationship between the effective data rate and the bit error rate is evaluated. As a result, the achievable data rate in the experiment of this study would be a remarkable considering the distance of the communication.